Armed Conflicts Are the Right to Establishment History of Arrival and Development (Eurasian Journal of Humanities and Social Sciences, 2022)
In this article, a number of manifestations of armed conflict today are manifested here and there on the globe. Even today, international arms conflicts, internal armed conflicts, as well as cases of armed violence have to be taken into account. It is highlighted based on historical experience that such cases require a high level of professionalism and a thorough knowledge of certain standards that must be followed even in emergencies caused by armed conflict.